Menakar Peran Kiai Dalam Pemilihan Presiden 2019 (Studi Di Provinsi Jawa Timur) - Dafis Ubaidillah Assiddiq (Journal of Governance Innovation, 2020)
This research is to examine the role of kiai in East Java province during the Indonesian presidential election in 2019. To find out what strategies were used by kiai and TKD (Tim Kampanye Daerah) Joko Widodo-KH. Ma'ruf Amin in East Java region also as several political figures who worked with JKSN (Jaringan Kiai Santri Nasional) to win Jokowi-Kiai  Ma'ruf.  The  type  of  research  used  in  this  research  is descriptive qualitative using the case study method.  The data collection techniques used are interviews and documentation.  The purpose of this research is to describe the role of kiai with TKD and JKSN during the presidential election. The results of this research is that the role of kiai includes being opinion leaders, political mediators and vote getter.